Dynamic of dormancy and budburst of willow plants in Planalto Sul, Santa Catarina State, Brazil - Rech, Tássio Dresch; Zanette, Flávio; Brandes, Dieter; Amarante, Cassandro Vidal Talamini do (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the dynamic and heterogeneity of buds dormancy, and to evaluate the effect of shoot harvest period on willow plant buds breaking in Planalto Sul, Santa Catarina State, Brazil. One-year-old shoots were collected between April and August of 2005 in the counties Lages, Bocaina do Sul, and Urupema. Bud dormancy was evaluated in basal (0 to 12 cm), middle (12 to 24 cm), and distal (24 to 36 cm) cuttings of the shoots. Cuttings with and without reduction to one bud were evaluated. The budburst of willow plants was also evaluated under field conditions. The deepest bud dormancy of basal shoots occurred in May, when the intensity of dormancy and frequency of dormant buds decreased from the top to the bottom of shoots. The harvest of willow shoots in April induced bud break before winter and hampered the budburst in spring.